Comparison of advanced therapy medicinal product gingiva and skin substitutes and their in vitro wound healing potentials. (22nd June 2017) - Boink, Mireille A.; Roffel, Sanne; Breetveld, Melanie; Thon, Maria; Haasjes, Michiel S.P.; Waaijman, Taco; Scheper, Rik J.; Blok, Chantal S.; Gibbs, Susan
Abstract: Skin and oral mucosa substitutes are a therapeutic option for closing hard‐to‐heal skin and oral wounds. Our aim was to develop bi‐layered skin and gingiva substitutes, from 3 mm diameter biopsies, cultured under identical conditions, which are compliant with current European regulations for advanced therapy medicinal products. We present in vitro mode of action methods to (i) determine viability: epithelial expansion, proliferation (Ki‐67), metabolic activity (MTT assay); (ii) characterize skin and gingiva substitutes: histology and immunohistochemistry; and (iii) determine potency: soluble wound healing mediator release (enzyme‐linked immunosorbent assay). Both skin and gingiva substitutes consist of metabolically active autologous reconstructed differentiated epithelium expanding from the original biopsy sheet on a fibroblast populated connective tissue matrix (donor dermis). Gingival epithelium expanded 1.7‐fold more than skin epithelium during the 3 week culture period. The percentage of proliferating Ki‐67‐positive cells located in the basal layer of the gingiva substitute was >1.5‐fold higher than in the skin substitute. Keratins 16 and 17, which are upregulated during normal wound healing, were expressed in both the skin and gingiva substitutes. Notably, the gingiva substitute secreted higher amounts of key cytokines involved in mitogenesis, motogenesis and chemotaxis (interleukin‐6 > 23‐fold, CXCL8 > 2.5‐fold) as well as higher amounts of the anti‐fibrotic growth factor, hepatocyte growth factor (>7‐fold), compared with the skin substitute. In conclusion, while addressing the viability, characterization and potency of the tissue substitutes, important intrinsic differences between skin and gingiva were discovered that may explain in part the superior quality of wound healing observed in the oral mucosa compared with skin.